New Developments in Anxiety Disorders - Durbano, Federico; Marchesi, Barbara (IntechOpen, 2016)
This book collects the contribution of a selected number of clinical psychiatrists, interested in the clinical application of some aspects of neurobiology of anxiety. The seven chapters of the book address some issues related to the latest acquisitions of neurobiology, in particular those aspects that are related to responses to treatment - both psychological and pharmacological. Some chapters are also dedicated to the comorbidities, a rule rather than an exception when it comes to anxiety. Each author summarized the clinical importance of his work, underlining the clinical pitfalls of this new book on anxiety.